2009
DOI: 10.1103/physrevb.80.193404
|View full text |Cite
|
Sign up to set email alerts
|

Spin-valve effect in zigzag graphene nanoribbons by defect engineering

Abstract: We report on the possibility for a spin valve effect driven by edge defect engineering of zigzag graphene nanoribbons. Based on a mean-field spin unrestricted Hubbard model, electronic band structures and conductance profiles are derived, using a self-consistent scheme to include gateinduced charge density. The use of an external gate is found to trigger a semiconductor-metal transition in clean zigzag graphene nanoribbons, whereas it yields a closure of the spin-split bandgap in the presence of Klein edge def… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
29
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 56 publications
(31 citation statements)
references
References 53 publications
2
29
0
Order By: Relevance
“…Similar results were also obtained in the O-doped case in which the E-field equaled 0.5-1.0 V=Å or −0.7 to −1.0 V=Å. Therefore, spin filters and spin switches can be achieved without magnetic contacts, 23) indicating promising applications for arsenene systems in spintronics.…”
supporting
confidence: 73%
“…Similar results were also obtained in the O-doped case in which the E-field equaled 0.5-1.0 V=Å or −0.7 to −1.0 V=Å. Therefore, spin filters and spin switches can be achieved without magnetic contacts, 23) indicating promising applications for arsenene systems in spintronics.…”
supporting
confidence: 73%
“…In a brief report which compares a pristine and a Klein defect ZGNR, 43 it is found that with the presence of an external gate, the Klein edge defects result in a transition from pure spin current to a spin degenerate charge current that is close to the Fermi energy. Furthermore, with the inclusion of a Klein defect, the ZGNR exhibits a net magnetization with a spin split band gap.…”
Section: Magnetism Due To Edge Shapementioning
confidence: 99%
“…During the past few years, the spin-polarized version of molecular electronics, the so-called molecular spintronics which seeks to unite the advantages of molecular electronics with the benefits of using spin as an additional degree of freedom, has attracted enormous interests since it holds promise for the next-generation nanoelectronic devices with improved performance and enhanced functionality [4][5][6][7]. This novel discipline has a wide range of applications from highdensity data storaging to quantum computing [8,9]. In the field of molecular spintronics, much research has focused on the single-molecule magnets (SMMs), which are a class of metal-organic complex and possess desirable physical properties for spintronic applications, such as long spin relaxation time of spin-polarized carriers [10], long magnetization relaxation time [11], quantum tunneling of the magnetization [12], and Berry-phase interference [13].…”
Section: Introductionmentioning
confidence: 99%